2020
DOI: 10.3389/fpls.2020.01042
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific Variation in Drought Response of Three Populations of Cryptocarya alba and Persea lingue, Two Native Species From Mediterranean Central Chile

Abstract: An increase in the severity of drought events on Mediterranean climates highlights the need of using plant material adapted to drought during restoration efforts. Thus, we investigated between-population morpho-physiological differences in Cryptocarya alba and Persea lingue, two native species from Mediterranean central Chile, for traits that could effectively discriminate population performance in response to water restriction (WR) testing. Three populations from each species were subjected to WR treatment an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…In our study, SD and VLA of trees exhibited a decoupled pattern, which may be largely affected by LA. Prior research had mostly focused on the separate relationship of SD and VLA with LA ( Sack et al., 2012 ; Alvarez-Maldini et al., 2020 : Zhao et al., 2017 ) and it is uncommon for studies to take into account the impact of LA to SD-VLA relationship. Our study showed a significantly positive relationship between SD and LA in trees ( P <0.05), whereas VLA was unaffected by LA ( Supplementary Figure S1 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, SD and VLA of trees exhibited a decoupled pattern, which may be largely affected by LA. Prior research had mostly focused on the separate relationship of SD and VLA with LA ( Sack et al., 2012 ; Alvarez-Maldini et al., 2020 : Zhao et al., 2017 ) and it is uncommon for studies to take into account the impact of LA to SD-VLA relationship. Our study showed a significantly positive relationship between SD and LA in trees ( P <0.05), whereas VLA was unaffected by LA ( Supplementary Figure S1 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Carins Murphy et al (2012) found that leaf expansion resulted in the coordinated development of SD and VLA in Toona ciliate. However, other studies found that minor VLA is little affected by LA (Sack et al, 2012;Zhao et al, 2016), whereas SD and LA revealed different types of associations (Carins Murphy et al, 2014;Alvarez-Maldini et al, 2020). In fact, these differences may be caused by species differences.…”
Section: Introductionmentioning
confidence: 94%
“…Then, irrigation was interrupted, allowing a progressive decrease in substrate water content. The gravimetric substrate water content (GSWC, %) was calculated according to the following equation: where Pot is the weight of the pot at each measurement time, Pot dry is the weight of the pot with the substrate dried in an oven until achieving a constant weight, and Pot wet is the weight of the pots at container capacity [34].…”
Section: Drought Treatment Applicationmentioning
confidence: 99%
“…At the end of the desiccation experiment, three plants per cultivar (2) and irrigation treatment (2) (12 plants in total) were randomly selected for biomass and leaf area measurements. The specific leaf area (SLA) was obtained according to [34].…”
Section: Biomass and Leaf Area Measurementsmentioning
confidence: 99%
“…Climate change is expected to decouple forest tree populations from the climates to which they have become locally adapted over many generations [1][2][3][4]. Local adaptation can involve critical trade-offs; frequently, populations from colder sites are more frost resistant, although they have less growth potential than populations from warmer locations that have genetically extended growing seasons [5][6][7], and populations from drier locations may be more drought resistant or tolerant [8,9]. Suitable climatic habitat for given biomes, tree species, and their populations is predicted to occur at more polar latitudes and higher elevations as climate change progresses [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%